Feasibility of the combined application of navigated probabilistic fiber tracking and navigated ultrasound in brain tumor surgery - Rückriegel, Stefan Mark; Bartsch, Andreas J. (World neurosurgery, 2016)
Background: Surgical resection of intra-axial tumors is a challenging procedure because of indistinct tumor margins, infiltration, and displacement of white matter tracts surrounding the lesion. Hence, gross total tumor resection without causing new neurologic deficits is demanding, especially in tumor sites adjoining eloquent structures. Feasibility of the combination of navigated probabilistic fiber tracking to identify eloquent fiber pathways and navigated ultrasonography to control brain shift was tested. Methods: Eleven patients with lesions adjacent to eloquent white matter structures (pyramidal tract, optic radiation and arcuate fascicle) were preoperatively subjected to magnetic resonance imaging including diffusion-weighted imaging on a 3-T magnetic resonance system (Trio [Siemens, Erlangen, Germany]). Probabilistic fiber tracking was performed using the tools of the FMRIB Software Library (FSL). Results of probabilistic fiber tracking and high-resolution anatomic images were integrated into the neuronavigation system Stealth Station (Medtronic, Minneapolis, Minnesota, USA) together with the navigated ultrasonography (SonoNav [Medtronic]). Results: FSL-based probabilistic fiber tracking depicted the pyramidal tract, the optic radiation, and arcuate fascicle anatomically plausibly. Integration of the probabilistic fiber tracking into neuronavigation was technically feasible and allowed visualization of the reconstructed fiber pathways. Navigated ultrasonography controlled brain shift. Conclusions: Integration of probabilistic fiber tracking and navigated ultrasonography into intraoperative neuronavigation facilitated anatomic orientation during glioma resection. FSL-based probabilistic fiber tracking integrated sophisticated fiber tracking algorithms, including modeling of crossing fibers. Combination with navigated ultrasonography provided a three-dimensional estimation of intraoperative brain shift and, therefore, improved the reliability of neuronavigation.
Gesehen am 08.02.2019